Design and molecular dynamics of multifunctional sulfonated poly(dimethylaminoethyl methacrylate)/mica hybrid cryogels through freezing-induced gelation. Issue 35 (22nd August 2019) - Okten, Nur Sena; Tanc, Beril; Orakdogen, Nermin
Abstract : This article addresses various strategies that have been explored to design sulfonated poly(dimethylaminoethyl methacrylate)/mica hybrid-gels with optimized network parameters and mechanical/swelling properties. Abstract : This article addresses various strategies that have been explored to design sulfonated poly(dimethylaminoethyl methacrylate)/mica hybrid-gels with optimized network parameters and mechanical/swelling properties. A series of hybrid cryogels and hydrogels containing amino and sulfonic acid groups were prepared from N, N -dimethylaminoethyl methacrylate (DMAEMA) and 2-acrylamido-2-methyl-1-propane sulfonic acid in the presence of inorganic additive mica via a cryogelation process and conventional in situ copolymerization. Cryogelation was used to fine-tune the mechanical properties of the PDMAEMA-based hybrid gels. The effects of pH, temperature and mica content on the network parameters, mechanical properties and swelling behavior were discussed. X-ray diffractometry and Fourier transform infrared spectroscopy confirmed that mica particles had participated in (cryo)polymerization, and the thermal stability and surface morphologies were improved by the addition of mica. The profile of water loss, decomposition of amine groups and breakdown of PDMAEMA chains of the resulting hybrid gels were determined by thermogravimetric analysis. A critical mica concentration was found for the hybrid hydrogels where the degree of swelling attains a maximum value. Below 0.50% (w/v) of mica, the ionic nature of mica dominates its crosslinker effect. The hybrid cryogels were tough and able to recover at room temperature after compression testing. The prepared hybrid-gels showed an enhanced swelling response and on–off switching swelling characteristics in water and in aqueous NaCl solutions. The parameters of equilibrium swelling, the initial swelling rate, the diffusional exponent, and the diffusion coefficient were evaluated and the swelling kinetics of the hybrid hydrogels and cryogels in water followed the pseudo second order model. All the prepared hybrid hydrogel and cryogel materials with tunable mechanical stability and elasticity can be excellent candidates for designing smart materials.